Etika dan Profesi Notaris: Akibat Sanksi atas Pelanggaran Kode Etik - Margareth Tutut Maharani Prakoso; Sukirno Sukirno (SIGn Jurnal Hukum, 2023)
This study aims to examine the legal position of the Code of Ethics for the Notary Public in legislation, and also seeks to analyze the consequences of sanctions for violating the code of ethics in the Notary profession. This study uses normative legal research with the statute and conceptual approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that the INI acts as the sole organization for Notaries in Indonesia, asserting its authority in establishing and enforcing the code of ethics. The code of ethics is established and enforced in various sanctions imposed, including admonishments, warnings, temporary suspensions, honorable dismissals, and dishonorable dismissals. However, such membership dismissals do not affect the status of a Notary as a Public Official. Nevertheless, severe violations of the code of ethics can prompt the Honorary Council to recommend the dismissal of a Notary to the Minister of Law and Human Rights. Therefore, several recommendations can be proposed to the relevant parties. First, the INI should continue to enhance its members’ understanding of the code of ethics through various educational activities and training. Second, the Honorary Council is expected to be more proactive in supervising and auditing Notary practices to detect and quickly address violations of the code of ethics. Lastly, the Minister of Law and Human Rights should carefully consider the dismissal recommendations from the Honorary Council and ensure that each decision is based on robust and fair evidence. Concurrently, closer cooperation between the Minister of Law and Human Rights and the INI is necessary to enforce the code of ethics and relevant legislation. Thus, the involvement and roles of all stakeholders are crucial in maintaining public trust in the Notary profession in Indonesia.